Relationship of Lower Urinary Tract Symptoms with Post Void Residual Urine and Prostatic Volume: Lower Urinary Tract Symptoms with Post Void Residual Urine and Prostatic Volume - Fazal, Muhammad Zohaib; Hussain, Syed Atif; Ghauri, Shafi; Haris, Saddiq; Sajjad, Muhammad; Afzal, Muhammad Imran (Pakistan Journal of Health Sciences, 2025)
Benign prostatic hyperplasia (BPH) is a frequent occurrence in older male. Objectives: To assess the correlation between International Prostate Symptoms Score (IPSS), prostate volume, and post-void residual volume (PVR). Methods: This was an analytical cross-sectional study conducted in the Urology Department of Sheikh Zayed Hospital, Rahim Yar Khan. Eighty-four men aged 40-70 years with BPH and LUTS for ≥ two months were recruited consecutively. Participants completed the IPSS, and PVR was assessed by abdominal sonography and prostate volume through transrectal ultrasound. A urinary tract infection was labelled by the growth of ≥ 105 CFU/ml of pathogenic microorganisms. Pearson correlation between IPSS and prostate volume and post-void urinary volume was calculated at 5% significance level. Results: Mean age was 57.9 ± 6.9 years, and 63.1% were ≤60 years of age. Mean prostate volume was 68.9 ± 17.0 cm³, and PVR was 191.5 ± 53.3 ml. Mean IPSS was 16.3 ± 6.4, with 67.9% having moderate LUTS. UTI prevalence was 54.8%. IPSS correlated positively and strongly with prostate volume (r = 0.911) and PVR (r = 0.920; p<0.001). UTI was more common in patients >60 years (80.6% vs. 39.6%) and in those with moderate (56.1%) and severe (100%) versus mild (13.3%) LUTS. Conclusions: IPSS showed a positive correlation with prostate volume and PVR, highlighting the utility of combined symptom scoring and ultrasound in managing benign prostatic enlargement.